+0  
 
0
10
1
avatar+1616 

Let a and b be the solutions to 7x^2 + x - 5 = 6x^2 - 4x + 5.  Compute (a - 4b)(b - 4a).

 Mar 19, 2024
 #1
avatar+128794 
+1

Simplify as

x^2 + 5x - 10 =  0

 

ab  = -10

a + b =  -5   square both sides

a^2 + 2ab + b^2   =  25

a^2 + b^2  + 2(-10)  = 25

a^2 + b^2  = 45

 

(a - 4b) ( b  -4a)  =

 

ab - 4b^2 - 4a^2 + 16ab  =

 

17ab  - 4 ( a^2 + b^2)  

 

17 (-10)  -  4 (45)  =

 

-170 - 180  =

 

-350

 

cool cool cool

 Mar 19, 2024

5 Online Users

avatar
avatar
avatar